Bibliometric Analysis of Press Freedom: Trends, Patterns, and Key Research Areas - Gita Pratiwi; Hanny Hafiar; Pandan Yudhapramesti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2026)
Press freedom serves as a fundamental pillar within a democratic system, ensuring that journalists can perform their role as social watchdogs without the shadow of intimidation. Globally, however, the integrity of this profession faces systemic challenges ranging from physical aggression to repression by state actors and interest groups. This study employs bibliometric analysis to map the evolving landscape of press freedom, identifying key trends, influential actors, and emerging themes within global scholarly literature. A total of 602 peer-reviewed articles indexed in Scopus from 1989 to 2025 were analyzed using Biblioshiny and VOSviewer, revealing a robust annual growth rate of 13.02% with a peak of 82 publications in 2025. The co-word network analysis identifies